Does Homeownership Promote Wealth Accumulation? - Leo Kaas; Georgi Kocharkov; Edgar Preugschat (Center for Economic Studies and ifo Institute (CESifo), 2016)
It is well known that homeowners are richer than renters, even after controlling for observable characteristics. This is often used as an argument for policies that foster homeownership. However, the causal link between homeownership and wealth is difficult to establish due to many potential sources of endogeneity. Utilizing the Household Finance and Consumption Survey for the Euro area, we correct for endogeneity by using inheriting the household's main residence as an instrument. The exclusion restriction is that conditional on the total amount of inheritance, inheriting a home affects the wealth position of the household only through homeownership. For the sample of inheritors we find that the local average treatment effect for households that inherit a home and stay homeowners is negative. Owning a home reduces riches due to sizable reductions in the net holdings of financial and other real wealth of the treated households.
Keywords: E21; D14; D31; C26; 330; homeownership; wealth accumulation; inheritance; instrumental variables